Health services access, utilization, and barriers for Arabic-speaking refugees resettled in Connecticut, USA - Ali Elreichouni; Sarah Aly; Kaitlin Maciejewski; Islam Salem; Noah Ghossein; M. Salah Mankash; James Dziura; Hani Mowafi (BMC, 2022)
Abstract Background Arabic-speaking refugees are the largest group of refugees arriving in the United States since 2008, yet little is known about their rates of healthcare access, utilization, and satisfaction after the end of the Refugee Medical Assistance (RMA) period. Methods This study was a cross-sectional observational study. From January to December 2019, a household survey was conducted of newly arrived Arabic-speaking refugees in Connecticut between 2016 and 2018. Households were interviewed in Arabic either in person or over the phone by one of five researchers. Descriptive statistics were generated for information collected on demographics, prevalence of chronic conditions, patterns of health seeking behavior, insurance status and patient satisfaction using the Patient Satisfaction Questionnaire (PSQ-18). Results Sixty-five households responded to the survey representing 295 Arabic-speaking refugees - of which 141 (48%) were children. Forty-seven households (72%) reported 142 chronic medical conditions among 295 individuals, 62 persons (21%) needed daily medication, 285 (97%) persons were insured. Median patient satisfaction was > 4.0 out of 5 for 6 of 7 domains of the PSQ-18 but wide variation (scores from 1.0 - 5.0). Conclusion Arabic-speaking refugees in Connecticut participating in this study were young. The majority remained insured after their Refugee Medical Assistance lapsed. They expressed median high satisfaction with health services but with wide variation. Inaccessibility of health services in Arabic and difficulty obtaining medications remain areas in need of improvement.